2012
DOI: 10.1111/j.1399-3054.2012.01670.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome expression profile analysis reveals important transcripts in maize roots responding to the stress of heavy metal Pb

Abstract: Lead (Pb) has become one of the most abundant heavy metal pollutants of the environment. With its large biomass, maize could be an important object for studying the phytoremediation of Pb-contaminated soil. In our previous research, we screened 19 inbred lines of maize for Pb concentration, and line 178 was identified to be a hyperaccumulator for Pb in both the roots and aboveground parts. To identify important genes and metabolic pathways related to Pb accumulation and tolerance, line 178 was underwent genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 48 publications
2
32
0
1
Order By: Relevance
“…They include genes that code for proteins involved in antioxidant systems, in particular, ascorbate peroxidase , antioxidant enzymes (Ghelich et al 2014), transport proteins (e.g., yeast protein YCF1 (Song et al 2003) and certain metal transporters ), plants chelate proteins (e.g., phytochelatins (Ghelich et al 2014) and metallothionein ), and secondary metabolites that act as reactive oxygen species (ROS) scavengers and metal chelators (Ghelich et al 2014). The toxicity effects of Pb and detoxification mechanisms in plants have been studied widely (Ghelich et al 2014;Qi et al 2015;Shen et al 2013;Song et al 2003); however, the mechanisms that regulate flowering and oxygen production in Pb-stressed P. acerifolia have not been reported at the transcriptome level. The basic mechanisms associated with plant tolerance to nonessential metal ions have been reported, but the biochemical mechanisms and transcriptome level changes involved in Pb tolerance remain largely unknown in P. acerifolia.…”
Section: Responsible Editor: Philippe Garriguesmentioning
confidence: 99%
See 1 more Smart Citation
“…They include genes that code for proteins involved in antioxidant systems, in particular, ascorbate peroxidase , antioxidant enzymes (Ghelich et al 2014), transport proteins (e.g., yeast protein YCF1 (Song et al 2003) and certain metal transporters ), plants chelate proteins (e.g., phytochelatins (Ghelich et al 2014) and metallothionein ), and secondary metabolites that act as reactive oxygen species (ROS) scavengers and metal chelators (Ghelich et al 2014). The toxicity effects of Pb and detoxification mechanisms in plants have been studied widely (Ghelich et al 2014;Qi et al 2015;Shen et al 2013;Song et al 2003); however, the mechanisms that regulate flowering and oxygen production in Pb-stressed P. acerifolia have not been reported at the transcriptome level. The basic mechanisms associated with plant tolerance to nonessential metal ions have been reported, but the biochemical mechanisms and transcriptome level changes involved in Pb tolerance remain largely unknown in P. acerifolia.…”
Section: Responsible Editor: Philippe Garriguesmentioning
confidence: 99%
“…Heavy metals also affect plant development either by depositing on the surfaces of plants or by entering the plant cells (Ernst et al 1983;Jordao et al 2006). Heavy metal contaminants arise mainly from anthropogenic activities, such as the unsystematic use of pesticides, discharge of untreated industrial wastes and effluents, illegal solid waste disposal and dumping, high burning rate of fossil fuels, and mining (Jiang et al 2014;Salt et al 1995;Shen et al 2013;Wang et al 2013). Lead (Pb) is a toxic metal that is stably persistent in soil and is easily taken up by plants but is hard to degrade (Chen et al 2000;Kanwal et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in hyperaccumulator inbred line 178, we found that DGEs were significantly changed association with lipid transport and metabolism pathway under Pb treatment [20]. In this study, we used the RNAseq approaches to investigate the gene expression changes associated with the successive time process induced in maize roots by Pb (Pb1000).…”
Section: Discussionmentioning
confidence: 99%
“…b-Expansin responded similarly in leaves and shoots (Geilfus et al, 2011). Moreover, the levels of sucrose synthase 1, cytosolic 3-phosphoglycerate ( Shen et al, 2013) kinase, fructokinase 2, and voltage-dependent anion channel protein were found to be increased in the root proteome and are involved in glucose metabolism, phosphorylation, fructose activation, and metabolism transport, respectively . Recently, Meng et al (2014) monitored the alterations in seed proteomes when the seeds were treated with NaCl.…”
Section: Salinitymentioning
confidence: 96%
“…A genome expression profile analysis of maize roots has also revealed important transcripts in the response to Pb stress (Shen et al, 2013). Under Pb stress, more than 4000 genes were found to be differentially regulated.…”
Section: Metal Toxicitymentioning
confidence: 99%